2008
DOI: 10.1210/en.2008-0008
|View full text |Cite
|
Sign up to set email alerts
|

Starvation and Triglycerides Reverse the Obesity-Induced Impairment of Insulin Transport at the Blood-Brain Barrier

Abstract: Insulin in the brain acts as a satiety factor, reduces appetite, and decreases body mass. Altered sensing by brain of insulin may be a leading cause of weight gain and insulin resistance. A decrease in the transport across the blood-brain barrier (BBB) of insulin may induce brain insulin resistance by inducing obesity. We here report that transport of iv administrated insulin across the BBB of obese mice, as measured by multiple-time regression analysis, was significantly lower than that in thin adult mice. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 43 publications
6
96
2
Order By: Relevance
“…Thus the question arises as to whether insulin resistance may be contributing to the leptin resistance observed with fructose feeding. This possibility seems unlikely, however, in light of the recent finding that in contrast to their effects on leptin, elevated circulating TGs enhance BBB insulin transport (67).…”
Section: Is the Phenomenon Specific To Fructose?mentioning
confidence: 98%
“…Thus the question arises as to whether insulin resistance may be contributing to the leptin resistance observed with fructose feeding. This possibility seems unlikely, however, in light of the recent finding that in contrast to their effects on leptin, elevated circulating TGs enhance BBB insulin transport (67).…”
Section: Is the Phenomenon Specific To Fructose?mentioning
confidence: 98%
“…Moreover, it was recently demonstrated that astrocytic IR deficiency decreases nutrient availability in the CNS, impairing systemic glucose homeostasis through the reduction in glucose-induced activation of glucose-sensing neurons [34]. Several studies have proposed that insulin transport into the brain is impaired in obesity and diabetes [51,57,58]. However, the lower rate of radiolabeled insulin transport observed in obese mice could be a result of hyperinsulinemia in these animals.…”
Section: Insulin Transport Into the Brainmentioning
confidence: 99%
“…Metabolic insults can reduce the ratio of insulin uptake into the brain, and it is thought that insulin transport is impaired under those circumstances [51,57,58]. However, in obese animals, brain insulin resistance is also observed at the level of hypothalamic signaling pathways with a decrease in PI3K-Akt response following insulin administration [91].…”
Section: Impaired Insulin Signaling In the Brain Upon The Onset Of Obmentioning
confidence: 99%
“…Levels of glucose are detected by nutrientsensing systems in both the periphery (15,41,56,130,212) and brain (111,130), with consequences to energy balance and fuel utilization in the periphery. TGs may even be sensed via their putative effects on leptin and insulin transport across the blood-brain barrier (13,108,232). However, FFAs present the most intriguing of these nutrients, as their impact on energy balance regulation may be most relevant during the dynamic metabolic state of overfeeding.…”
Section: Enhanced Metabolic Flexibility: Improved Nutrient Clearancementioning
confidence: 99%